2011
DOI: 10.1007/s00774-011-0264-x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hypovitaminosis D in pregnant Japanese women with threatened premature delivery

Abstract: Serum 25-hydroxyvitamin D (25-OHD) concentrations are thought to accurately reflect vitamin D stores, and vitamin D deficiency causes secondary hyperparathyroidism, irreversible bone loss, and increased risk of fracture. Recent studies suggest that decrease of serum 25-OHD level in mothers could increase the risk of preeclampsia, cesarean section, and craniotabes. Furthermore, this deficiency may affect bone mass and the incidence of neuromuscular diseases of their children in the future. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
73
5
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 31 publications
12
73
5
6
Order By: Relevance
“…In present study significant (P = 0.001) increase number of preterm birth were found among control group who were vitamin D deficient with mean vitamin D levels <50 nmol/l as compare to study group who were supplemented with vitamin D and had sufficient vitamin D with mean vitamin D levels >50 nmol/l. As compare to present study Shibata M et al (2011) 29 also found high prevalence hypovitaminosis D in pregnant Japanese women with serum concentration of vitamin significantly low in women with preterm labour (11.2 ± 3.2 ng/ml) in comparison with term controls, (15.6 ± 5.1 ng/ml).…”
Section: Discussionsupporting
confidence: 65%
“…In present study significant (P = 0.001) increase number of preterm birth were found among control group who were vitamin D deficient with mean vitamin D levels <50 nmol/l as compare to study group who were supplemented with vitamin D and had sufficient vitamin D with mean vitamin D levels >50 nmol/l. As compare to present study Shibata M et al (2011) 29 also found high prevalence hypovitaminosis D in pregnant Japanese women with serum concentration of vitamin significantly low in women with preterm labour (11.2 ± 3.2 ng/ml) in comparison with term controls, (15.6 ± 5.1 ng/ml).…”
Section: Discussionsupporting
confidence: 65%
“…1 Vitamin D status at birth and during early infancy, when breast milk is the predominant source of nutrition, is determined by maternal vitamin D status. 2,3 Contemporary population-and primary care-based studies of pregnant women have shown a high prevalence of serum 25(OH)D ,20 ng/mL in Asia (70%-96%), [4][5][6] Australia (10%-47%), [7][8][9][10] Europe (15%-44%), 11,12 the United Kingdom (49%-75%), [13][14][15] India (74%), 16 and the United States (37%). 17 Although less completely studied at the population level, in primary care-based studies from the United States, serum 25(OH)D ,20 ng/mL is present in 11% to 12% of infants.…”
mentioning
confidence: 99%
“…Despite the fact that daily prenatal vitamin D supplementation is advised and observed in most countries, an alarmingly high prevalence of vitamin D insufficiency has been demonstrated in nearly all populations studied [19][20][21]. There is a growing concern about the various adverse health impacts of vitamin D deficiency during pregnancy may have on mother as well as on fetus and later in life [6].…”
Section: Discussionmentioning
confidence: 99%
“…Bodnar LM et al [10], conducted a nested case-control study and found that adjusted serum 25 A Japanese retrospective study found mothers with threatened premature delivery had significantly lower 25-0HD levels (11.2±3.2 ng/ml) than those in mothers with normal delivery (15.6±5.1 ng/ ml) [27]. Recently a multi centre study involving US cohort of twin pregnancies showed an independent association between maternal 25-hydroxyvitamin D concentrations at 24-28 weeks of gestation and preterm birth [28].…”
Section: Discussionmentioning
confidence: 99%